King & kayla and the case of the secret code eaudiobook - Butler, Dori Hillestad (King & Kayla, 2019)
A lovable dog helps his human girl solve a mystery Kayla and Mason both got mysterious letters written in code What does Kayla know The same person left both letters It s someone she and Mason both know The two letters are the same except for the second word What does King know Jillian left the letters What do the letters say A loveable dog helps his human girl solve a mystery Kayla and Mason both got mysterious letters written in code What does Kayla know The same person left both letters It s someone she and Mason both know The two letters are the same except for the second word What does King know Jillian left the letters What do the letters say